Prevalence of sarcopenia in older Chinese adults: a systematic review and meta-analysis - Xin Sun; Li Lu; Caihong Xin; Ling Shan (BMJ Open)
Objective This meta-analysis was conducted to estimate the overall prevalence of sarcopenia in older Chinese adults.Design Systematic review and meta-analysis.Participants A literature research was conducted using the PubMed, Web of Science, China National Knowledge Infrastructure, CQVIP and Wanfang databases. The following search terms in the abstract were used: “sarcopenia” in combination with the terms “prevalence,” “epidemiology” and “China.” All studies published from January 2010 to November 2020 were included. The random-effect model was used to estimate the prevalence of sarcopenia. The sex-specific prevalence of sarcopenia at a 95% CI was also calculated using different criteria for defining sarcopenia.Primary outcome measures The overall prevalence of sarcopenia in older Chinese adults.Results In total, 23 articles were included in this meta-analysis involving 21 564 participants. On the basis of the Asian Working Group for Sarcopenia criterion, the overall prevalence of sarcopenia among the elderly in China was 14% (95% CI 11% to 18%); the prevalence was higher in Chinese women than in men (15% vs 14%).Conclusions This systematic review is the first estimation of the pooled prevalence of sarcopenia in older Chinese adults. Our results suggest that China has a large number of patients with sarcopenia. These findings would be useful for sarcopenia prevention in China. There is a high degree of heterogeneity, and although there are a large number of cases and could be an emerging public health issue, more research is required to make these claims.PROSPERO registration number CRD42020223405.